Desire, Duplicity and Narratology: Boris Vian's L 'Ecume des jours - Charles J. Stivale (Studies in 20th & 21st Century Literature, 1993)
In this examination of Boris Vian's L'Ecume des jours, I call into question the masculinist resistance to criticism of Vian and his works through a critical counter-resistance from a feminist narratological perspective. In order to examine the implications of "narrative desire" for understanding textual and sexual difference, I argue for a narratology that develops the concept of textual "seduction" as a question of narrative duplicity. I undertake this "re-reading" not merely from the perspective of an "ideological unmasking," but also to suggest the possibility of a positive hermeneutic, or more precisely, the limits of such a move given inherent difficulties evident in Vian's text. L'Ecume des jours provides the ground for reflections linking narratology to critical strategies that will enable me to pursue three lines of inquiry: first, how do the diegetic episodes depicting the parallel obsessions of the chief male protagonists, Colin and Chick, mask crucial questions of sexual difference in the story? Second, to what extent do the narrator's means of engaging the reader serve to actualize or obscure questions of sexual difference and narrative duplicity? Third, how does the novel's extensive recourse to dialogue contribute both to the occupation of the narrator's role and to the apparent neutralization of sexual differentiation?
Keywords: L& #x27; Ecume des jours; Boris Vian; masculinist resistance; literary criticism; feminist narratological perspective; feminism; feminist theory; narrative desire; textual seduction; narrative duplicity; sexual differences; male; female; dialogue